Jetty Sebagai Alternatif Pengaman Muara Sungai Air Bengkulu - Yudi Irawan (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
The problem that is often found in river estuaries is the silting/closing of the river mouth by sand sediments from the sea. Jetty as one of the alternative river estuary security buildings can anticipate the sedimentation of material grains at the mouth of the river caused by the influence of sea waves, tidal movement and sediment transport in the river channel. The type of jetty which is in accordance with the characteristics of the air Bengkulu river estuary is short type of jetty with construction from a pile of rocks and tetrapods. The tetrapods weight used ranges from 300 -710 kg at the end and jetty arm the weight of the rubble stone is used between 350 – 550 kg in two layers. The structure of the toe protector ( toe protection) on the jetty is made of piles of rock weighing 70 – 100 kg. the elevation of the jetty peak si planned to be as high as 5.63 m with a peak width of 2.69 kg. Thevalue of ? in location is 2.38 kg/cm2 ? tpermit for sand which 2.5 – 3.0 kg/cm2, so that footing subsoil is able to whitstand the load of the jetty on top of it.